Reform and Breakthrough in Business Regulations for Empowering MSMEs in Indonesia and the Netherlands - Riwanto, Agus; Suryaningsih, Sukarni; Putri, Delasari Krisda (Journal of Human Rights, Culture and Legal System, 2023)
There are too many overlapping MSMEs determination policies which result in hampering MSMEs empowerment. The dynamics of global change require a fast and responsive response because, without policy reformulation, economic growth will stagnate or even slow down. This article delves into the necessity of regulatory reform to enhance the ease of doing business for MSMEs, using the Omnibus Law method. Conducted as normative legal research, this study uses normative legal research and analyzes secondary data to examine the existing challenges. The findings reveal various obstacles faced by MSMEs, including complexities in obtaining business licenses, cumbersome tax payment systems, limited access to business capital, and the absence of a formal business entity. To address these regulatory issues, alternative solutions are proposed through the Omnibus Law method, emphasizing the simplification of regulations, fostering public participation, and harmonizing both vertical and horizontal regulations. Moreover, drawing lessons from the Netherlands, where the government established the Dutch Advisory Board on Regulatory Burdens (ATR) to reduce administrative burdens on SMEs, Indonesia can prioritize similar measures to simplify regulations and lower costs. By emulating the ATR's independent and collaborative approach, Indonesia has the potential to establish its own advisory body, fostering a supportive business environment for SMEs and promoting economic growth.